(untitled) (Revista Iberoamericana de Bioética, 2018)
Prenatal genetic diagnosis allows the identification of many autosomal recessive diseases in advance of embryo implantation. However, the therapeutic possibilities are still scarce for diagnosed individuals. For this reason, they are often eliminated through negative selection. A critical analysis of two issues is proposed: the concordance between the application of genetic tests and the principle of equal value. Subsequently, it is considered from a phenomenological approach, how significant human relationships such as filiation and genitoriality are modified.